Web Development Techniques and Remote Laboratories - Ursutiu, Doru; Iordache, Dragos; Cotfas, Petru Adrian; Cotfas, Daniel Tudor; Samoila, Cornel (International Journal of Online and Biomedical Engineering (iJOE), 2009)
In the actual context of the world economic and financial crisis, any source that causes economy is welcomed. In the technical educational system such a source is represented by the implementation of remote labs. These allow, among other things, the sharing of modern technology between several centers and also the saving of power by using an adequate energetic management. This paper presents a solution for implementing remote labs by using web technologies that are platform independent from the client point of view. Such a lab implementation exemplification is materialized by remote controlling the NI-ELVIS platform.